2016
DOI: 10.1001/jama.2015.18603
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Site of Death, Health Care Utilization, and Hospital Expenditures for Patients Dying With Cancer in 7 Developed Countries

Abstract: ; for the International Consortium for End-of-Life Research (ICELR) IMPORTANCE Differences in utilization and costs of end-of-life care among developed countries are of considerable policy interest. OBJECTIVE To compare site of death, health care utilization, and hospital expenditures in 7 countries: Belgium, Canada, England, Germany, the Netherlands, Norway, and the United States. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort study using administrative and registry data from 2010. Participants were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
386
8
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 433 publications
(436 citation statements)
references
References 35 publications
33
386
8
9
Order By: Relevance
“…It is possible that the cost of a hospital stay influences the need to find alternatives to hospitalization such as home or hospice. As reported in that study, the per diem cost for a hospital stay is relatively high in the United States, which could be one factor influencing hospital use 7 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It is possible that the cost of a hospital stay influences the need to find alternatives to hospitalization such as home or hospice. As reported in that study, the per diem cost for a hospital stay is relatively high in the United States, which could be one factor influencing hospital use 7 .…”
Section: Discussionmentioning
confidence: 60%
“…Those data will add to the existing body of research about end-of-life care for patients with cancer and offer new findings about interprovincial variation in the management of end-of-life care. An international comparative study of hospital use during the last 30 days of life found that, of 7 countries, Canada fell into the middle range for hospital use, including number of hospital days at the end of life for patients dying from cancer 7 . Patients spent 7.7 days in hospital at the end of life in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the CIHI have formed the basis for a substantial body of clinical and health services research. [13][14][15] We also obtained data about overall hospital patient volumes and bed use from the decision support department of each hospital.…”
Section: Data Collectionmentioning
confidence: 99%
“…15 Despite these limitations, four countries typically emerge at the top of all palliative care rankings-Australia, Ireland, New Zealand, and the United Kingdom (Table 2). Perhaps not surprisingly, these countries have developed the most comprehensive national strategies and began addressing the issue of universal access to palliative care over a decade ago.…”
Section: Barriers To Accessing High Quality Palliative Carementioning
confidence: 99%